SPE Middle East Oil &Amp; Gas Show and Conference 2021
DOI: 10.2118/204609-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing Fluid Design: A Closer Look at Breaker and Surfactant Selection

Abstract: Guar and its derivatives are the most commonly used gelling agents for fracturing fluids. At high temperature, higher polymer loadings are required to maintain sufficient viscosity for proper proppant carry and creating the fracture geometry. To minimize fracturing fluids damage and optimize fracture conductivity, it is necessary to design a fluid that is easy to clean up by ensuring proper breaking and sufficiently low surface tension for flow back. Therefore, breakers and surfactants must be carefully select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, due to the slow swelling rate of guar gum, they are prone to microbial degradation, so it is necessary to add bactericides . In addition, the biopolymers such as guar gum can cause significant formation damage through various mechanisms (core permeability damage rate of 10%–38%), which depend on factors such as polymer type, concentration, cross-linking agent, gel-breaker type or concentration, and rock permeability. , The application in high-temperature environments exacerbates this problem, as a high polymer loading is required, and polymer residues can hinder the flow of hydrocarbons. Yan et al reported that the core-damage rates of different fracturing fluids were guar gum (34.1%) > polymer (27.5%) > VES (8.8%).…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…However, due to the slow swelling rate of guar gum, they are prone to microbial degradation, so it is necessary to add bactericides . In addition, the biopolymers such as guar gum can cause significant formation damage through various mechanisms (core permeability damage rate of 10%–38%), which depend on factors such as polymer type, concentration, cross-linking agent, gel-breaker type or concentration, and rock permeability. , The application in high-temperature environments exacerbates this problem, as a high polymer loading is required, and polymer residues can hinder the flow of hydrocarbons. Yan et al reported that the core-damage rates of different fracturing fluids were guar gum (34.1%) > polymer (27.5%) > VES (8.8%).…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%